Anthropocene – Perspectives from the Environmental Humanities - Schmidt, Matthias; Soentgen, Jens; Zapf, Hubert (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
Originating from the geosciences, the concept of the Anthropocene is also the subject of lively and often controversial discussions in the humanities and social sciences. The aim of this paper is to present particular perspectives on the recently established Environmental Humanities on the Anthropocene, in order to outline the background behind the establishment of the Environmental Humanities, and to explain the central features and intentions of this inter- and transdisciplinary field. The emerging Environmental Humanities can be seen as the humanities seeking to contribute to the study, understanding and management of the ongoing global environmental crisis, i.e. a theme that has long been – and still is – dominated by the natural sciences. Drawing on concepts, theories and methods from not only the humanities, but also from social sciences, Environmental Humanities address “ fundamental questions of meaning, value, responsibility and purpose” (Rose et al. 2012: 1) in relation to the environment and environmental crises in a time of accelerating change. In doing so, environmental problems are seen as inseparable from social, cultural and human factors. At the same time, the Environmental Humanities pursue a normative claim to advance a responsible approach to the environment, in order to preserve a liveable world. Against this backdrop, broader questions open up on the concept of the Anthropocene, which not only go far beyond the question of the beginning and quantifiable extent of human influence on the geosphere, but also include questions on the causes, consequences, perceptions and interpretations, as well as responsibilities and outcomes, of the environmental crisis.